(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Irina A. Zubkova (Rostov-on-Don, Russian Federation) The article reveals therole of adverbial determinants with a qualitativelycharacterizing meaning in the actual (semantic) articulation of the statement. From the communicative point of view, statements containing determining circumstances in the composition of the theme/rheme receive additional possibilities in the realization of the author’s intention. Depending on the communicative task, the linguistic units under study may express the theme/ rheme on their own or be part of a complex theme/rheme. Special attention is paid to the issue of contextual connection of determinants with subsequent statements. Key words: adverbial determinant; current segmentation; given (subject); new (rheme); semantic center of expression; communicative task; intentional installation of the author. DOI 10.23683/1995-0640-2019-1-76-82